The importance of indigenous freshwater foods for rural women in Guadalcanal Province, Solomon Islands - Gomese, Chelcia; Wate, Jillian Tutuo; Alfred, Joy Ellen; Sendo, Evelyn; Tefetia, Malachi; Tepai, Jocelyn; Maike, Patricia; Pitakaka, Priscilla; Ride, Anouk; Eriksson, Hampus (Pacific Community (SPC), 2023)
Documents rural womens cooking practices and livelihoods focusing on lesser known aquatic foods. The article summarizes recipies used in a cooking competition among rural women and uses that as a platform for describing contemporary healthy and sustainable aquatic food systems.